Photocatalytic Degradation of Dichlorvos in Visible Light by Mg2+-TiO2 Nanocatalyst - T. Siva Rao; Teshome Abdo Segne; T. Susmitha; A. Balaram Kiran; C. Subrahmanyam (Advances in Materials Science and Engineering)
Photocatalytic activity of TiO2 was studied by doping with magnesium (Mg2+-TiO2) with varying magnesium weight percentages ranging from 0.75–1.5 wt%. The doped and undoped samples were synthesized by sol-gel method and characterized by X-ray diffraction (XRD), N2 adsorption-desorption (BET), X-ray photoelectron spectroscopy (XPS), UV-visible diffuse reflectance spectroscopy (DRS), and scanning electron microscopy (SEM). The XRD data has shown that anatase crystalline phase in Mg2+-TiO2 catalysts, indicating that Mg2+ ions did not influence the crystal patterns of TiO2. The presence of magnesium ions in TiO2 matrix has been determined by XPS spectra. DRS spectra showed that there is a significant absorption shift towards the visible region for doped TiO2. The SEM images and BET results showed that doped catalyst has smaller particle size and highest surface area than undoped TiO2. The photocatalytic efficiency of the synthesized catalysts was investigated by the photocatalytic degradation of aqueous dichlorvos (DDVP) under visible light irradiation, and it was found that the Mg2+-doped catalysts have better catalytic activity than undoped TiO2. This can be attributed that there is a more efficient electron-hole creation in Mg2+-TiO2 in visible light, contrary to undoped TiO2 which can be excited only in UV irradiation. The effect of dopant concentration, pH of solution, dosage of catalysts, and initial pesticide concentration has been studied.